Optimizing LTE-Advanced performance in urban networks using intra-band and inter-band carrier aggregation - Hasanah Putri; Radial Anwar; Alfin Hikmaturokhman (Institute of Advanced Engineering and Science, 2026)
The rapid increase in mobile data consumption has significantly impacted network performance, especially in densely populated urban areas. Long-term evolution (LTE)-Advanced, an enhancement of LTE under 3GPP Release 10, incorporates carrier aggregation (CA) to optimize spectral efficiency and data throughput. This study investigates the effectiveness of intra-band and inter-band CA methods in improving LTE-Advanced network performance in Cirangrang-Cibaduyut Kidul, a high-density urban area in Bandung, Indonesia. Using a combination of drive tests and network simulations in Atoll 3.3.0, Key performance indicators such as reference signal received power (RSRP), signal-to-interference-plus-noise ratio (SINR), and throughput were analyzed. The results indicate that inter-band CA outperforms intra-band aggregation, providing significant improvements in signal quality and data rates. These findings suggest that inter-band CA is a viable solution for optimizing LTE-Advanced networks in urban environments with high traffic demand. This research provides practical recommendations for network operators to enhance service quality efficiently without extensive infrastructure expansion.